(untitled) (Ustozlar uchun, 2026)
As we navigate the 2025-2026 flu season, the battle against the influenza virus remains one of the most complex challenges in modern pharmacology. This review examines the two primary pillars of defense: vaccines (preventative) and antivirals (reactive). We explore the shift from quadrivalent to trivalent vaccines following the extinction of the B/Yamagata lineage, the rise of mRNA technology in flu prevention, and the refined role of endonuclease inhibitors like Baloxavir marboxil. By synthesizing clinical data and public health outcomes, this article provides a comprehensive comparison of these two distinct pharmacological strategies, ultimately arguing for a synergistic approach guided by emerging AI-driven strain prediction.